QUALITY PERFORMANCE MEASUREMENTS AND STUDY OF WI-FI NETWORK AT RURAL NGN - WINNER (NIM: 13203174); Tim Pembimbing : Ir. Armein Z. R. Langi, M.Sc., Ph.D.; Dr. Yoanes , BERNHARD
Wi-Fi is a popular term for Wireless Local Area Network (WLAN). It is also based on the IEEE 802.11 specification. Wi-Fi was originally intended for the use of wireless devices and Local Area Networks (LANs), but it is now widely used for Internet access. The simple implementation of this technology, led Wi-Fi into rapid development, one of which is rural development in the area of NGN. Utilization of Wi-Fi technology has a lot of problems and obstacles that will cause the system not to work optimally. The main problems in the performance of wireless networks located at the physical layer in OSI, the parameters of Quality of Service (QoS). In addition to this, interference, multipath, delay spread also may decrease the quality of the network. The purpose of this study is to determine the performance of wireless Internet networks in rural areas by comparing the measurement results obtained based on the characteristics of network performance standards. In addition, this study also aimed to determine the appropriate time in conducting virtual classes on the Wi-Fi networks, especially in rural areas. This research was conducted by designing a measurement system to determine the performance of long-distance network of Wi-Fi at Punclut testbed network that connected to the Institute of Technology Bandung (ITB) campus network through a wireless radiolink of 2.4 GHz. Measurements of throughput, jitter and packet loss are generated by sending TCP and UDP traffic on the existing testbed network, while delay measurement is generated by sending Packet Internet Grouper on other computers that will be measured. The measurement results obtained compared with the general standard of performance of a network to determine the quality of the network to be measured.